2023
DOI: 10.1186/s12889-023-15878-3
|View full text |Cite
|
Sign up to set email alerts
|

The indirect impacts of nonpharmacological COVID-19 control measures on other infectious diseases in Yinchuan, Northwest China: a time series study

Abstract: Background Various nonpharmaceutical interventions (NPIs) against COVID-19 continue to have an impact on socioeconomic and population behaviour patterns. However, the effect of NPIs on notifiable infectious diseases remains inconclusive due to the variability of the disease spectrum, high-incidence endemic diseases and environmental factors across different geographical regions. Thus, it is of public health interest to explore the influence of NPIs on notifiable infectious diseases in Yinchuan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…RIDs, notably HFMD and mumps, displayed a pronounced susceptibility to PHSMs 27 . Conversely, the impact of PHSMs on BSTDs was more limited, consistent with previous research findings 9 , 10 , 26 . For most RIDs, the implementation of PHSMs significantly curtailed their transmission (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…RIDs, notably HFMD and mumps, displayed a pronounced susceptibility to PHSMs 27 . Conversely, the impact of PHSMs on BSTDs was more limited, consistent with previous research findings 9 , 10 , 26 . For most RIDs, the implementation of PHSMs significantly curtailed their transmission (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Although many published studies 9 13 have analyzed the impact of PHSMs on notifiable infectious diseases (NIDs), there remains a significant gap in our understanding of this relationship. Most of these studies 9 , 10 have focused primarily on the impact of PHSMs in their early stages and have tended to overlook the potential impact of PHSMs of varying durations. Additionally, most published studies have predominantly concentrated on the impact of PHSMs on common RIDs and IIDs, with limited quantitative analysis on BSTDs and ZIDs 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, we identified three turning points whose timings closely align with the implementation of NPIs in Ningxia. Previous studies 42 , 48 observed similar trends in other respiratory diseases. Therefore, we have reasons to believe that NPIs significantly influence the incidence of influenza.…”
Section: Discussionsupporting
confidence: 79%
“…Influenza reached its first peak period in 2019, with an incidence of 32.62/100,000. Then, we observed a remarkable decline in 2020, staying in step with the United States, Singapore, and China 42 44 . After nearly two years, influenza up-resurgence and reached another peak in 2022, as was reported in several studies before 15 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation